2018
DOI: 10.1017/s1047951118001658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathophysiological aspects of bicuspid aortic valve disease

Abstract: A bicuspid aortic valve is not only a common congenital heart defect but also an enigmatic condition that can cause a large spectrum of diseases, such as aortic valve stenosis and severe heart failure in newborns whereas aortic dissection in adults. On the contrary, a bicuspid aortic valve can also occur with normal function throughout life and never need treatment. Numerous genetic mechanisms are involved in the abnormal cellular functions that may cause abnormal development of the aortic valve during early f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 97 publications
1
18
0
11
Order By: Relevance
“…Today, BAV is defined as the existence of two valve leaflets, although there is great individual variability with regard to the valve detailed characteristics: symmetry, presence of raphe, nature of the commissures, etc. [1][2][3] . One of the leaflets is mainly generated by the fusion or lack of separation of two of the primitive leaflets during valve development.…”
Section: Anatomy and Morphological Subtypesmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, BAV is defined as the existence of two valve leaflets, although there is great individual variability with regard to the valve detailed characteristics: symmetry, presence of raphe, nature of the commissures, etc. [1][2][3] . One of the leaflets is mainly generated by the fusion or lack of separation of two of the primitive leaflets during valve development.…”
Section: Anatomy and Morphological Subtypesmentioning
confidence: 99%
“…Bicuspid aortic valve (BAV) is the most common congenital heart disease in the general population. Far from being just a harmless valve malformation, it entails a complex and heterogeneous disease 1 . Its spectrum can consist, at its most benign extreme, of an incidental finding, remaining as a subclinical anomaly throughout life, or, at a more serious extreme, become the origin of a valve dysfunction that may be decisive for patient short-term prognosis 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent survey revealed that of all the individuals with BAV, 75% of BAV patients will be presenting aortic valve stenosis and dilation of the supra-coronary aorta, 15% aortic insufficiency and dilation of the proximal aortic root, leaving the fate of the remaining 10% undefined [1,2]. These enlist the absence or presence of raphes, if yes then numbers were noted, spatial position of cusps or raphes, and functional status of the valve [3]. Aortic valve repair avoids anticoagulation and prosthetic valverelated this could provide many advantages for patients with BAV, but the prosthetics valve replacement remains the most reliable choice of treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Вступ. Двостулковий аортальний клапан (ДАК) є найчастішою вродженою вадою серця, що має популяційну частоту 1-2 % [1]. За даними А. С. Шарикіна (2016) [2], ДАК слід розцінювати як серйозну серцеву ваду, що може призводити до розвитку стенозу або недостатності клапана та супроводжується розширенням кореня аорти з порушенням гемодинаміки, гіпертрофією лівого шлуночка та загрозою розшарування аорти, а не як малу аномалію серця, що не впливає на кровообіг, як вважали раніше, що потребує диспансерного спостереження за хворими, починаючи з раннього віку.…”
unclassified